Adjuvant radiotherapy following neo-adjuvant chemotherapy and surgery in oesophageal cancer: a retrospective cohort study of survival - Teoh, S; Virdee, PS; Mason, J; Patel, K; Warner, N; Hobbs, C; Sabbagh, A; Marshall, RE; Maynard, ND; Sgromo, B; Gillies, RS; Streets, CG; et al. (National Cancer Research Institute, 2018)
Following surgery for oesophageal cancer, positive circumferential resection margin (CRM) (R1), defined as margin <1mm, is an associated predictor of poor survival. The role of selective adjuvant radiotherapy in patients with R1 margin following neo-adjuvant chemotherapy (NACT) is unclear. We investigated survival outcomes following adjuvant radiotherapy in patients undergoing NACT with R1 margin from oesophageal surgery.